Keragaman Penghidupan Rumah Tangga Petani Padi Sawah Tadah Hujan (Studi Kasus di Kecamatan Kroya Kabupaten Indramayu) - Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa; Charina, Anne (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Farmer households in rural areas tend to adopt multiple livelihood patterns as a livelihood strategy. Limited income in the agricultural sector causes farmers to develop strategies to sustain their lives. This paper aims to analyze the diversity of livelihoods of rice farming households on rainfed land. This research uses a qualitative design with a case study technique. Informants in this study were farmer households and community leaders. Data were analyzed descriptively. The results show that livelihood strategies are related to three main things: the availability of opportunities, the existence of capabilities and the diversity of livelihood options. One of the factors that determine the livelihood strategies adopted by farmer households is related to the employment opportunities available in the village as well as opportunities that come from both inside and outside the village.